The spiritual journey of infertile couples: discussing the opportunity for spiritual care - Romeiro, Joana (2017)
Infertility is a worldwide public health issue that exerts an in-depth impact on couples, families, communities and the individual. This reproductive health condition, along with fertility treatments, often forces couples to question their purpose and meaning in life, and to begin a spiritual journey. Nursing and midwifery literature describes the care of those living with infertility, but often lacks a clear approach of the spiritual dimension, and diagnosis and interventions may not be effectively addressed. In this paper, we present a discussion about spirituality and the assessment of spiritual needs such as hope, beliefs, meaning and satisfaction in life. In addition, spiritual needs are defined, for both nurses and midwives, and spiritual interventions are proposed for promoting couples’ resilience and spiritual well-being. Spirituality should be considered from the beginning to the end of life. It is necessary to translate this into the development and implementation of both specific policies regarding a spiritual approach and advanced education and training programs for nurses and midwives who care for infertile couples.